Field Epidemiology Training Programmes in Africa - Where are the Graduates? - Mukanga David; Namusisi Olivia; Gitta Sheba N; Pariyo George; Tshimanga Mufuta; Weaver Angela; Trostle Murray (BMC, 2010)
Abstract Background The current shortage of human resources for health threatens the attainment of the Millennium Development Goals. There is currently limited published evidence of health-related training programmes in Africa that have produced graduates, who remain and work in their countries after graduation. However, anecdotal evidence suggests that the majority of graduates of field epidemiology training programmes (FETPs) in Africa stay on to work in their home countries--many as valuable resources to overstretched health systems. Methods Alumni data from African FETPs were reviewed in order to establish graduate retention. Retention was defined as a graduate staying and working in their home country for at least 3 years after graduation. African FETPs are located in Burkina Faso, Ethiopia, Ghana, Kenya, Nigeria, Rwanda, South Africa, the United Republic of Tanzania, Uganda and Zimbabwe. However, this paper only includes the Uganda and Zimbabwe FETPs, as all the others are recent programmes. Results This review shows that enrolment increased over the years, and that there is high graduate retention, with 85.1% (223/261) of graduates working within country of training; most working with Ministries of Health (46.2%; 105/261) and non-governmental organizations (17.5%; 40/261). Retention of graduates with a medical undergraduate degree was higher (Zimbabwe 80% [36/83]; Uganda 90.6% [125/178]) than for those with other undergraduate qualifications (Zimbabwe 71.1% [27/83]; Uganda 87.5% [35/178]). Conclusions African FETPs have unique features which may explain their high retention of graduates. These include: programme ownership by ministries of health and local universities; well defined career paths; competence-based training coupled with a focus on field practice during training; awarding degrees upon completion; extensive training and research opportunities made available to graduates; and the social capital acquired during training.